Fibroma desmoides managed in Third Chair and Department of Surgery of University School of Medical Sciences in Poznań - Paszkowski, Jacek; Drews, Michał; Krokowicz, Piotr; Banasiewicz, Tomasz; Wierzbicki, Tomasz (Contemporary Oncology/Współczesna Onkologia, 1999)
Desmoids are rare tumours originating from musculo-aponeurotic soft tissues with their own biology between fibroma and fibrosarcoma. They are more common in patients with familial adenomatous polyposis (FAP). Eight patients with desmoid tumours have been operated in Third Chair and Department of Surgery of Karol Marcinkowski Medical University in Poznań, Poland. Age ranged from 18-40 years. All patients underwent restorative proctocolectomy because of FAP. In all patients desmoid appeared after trauma (usually operation). Additional therapy (radiotherapy, chemotherapy, NSAID, hormonal agents) was performed in five patients with diagnostic or palliative operation. All patients are alive. Our experience confirm the conclusion that the wide-field resection is the treatment of choice for desmoid tumours.